Changes in the growth, photosynthesis, and nitrogen allocation characteristics of hydroponically grown lettuce under different nitrate levels in a nutrient solution - Jung, Dae Ho; Choi, Sooyoung; Lee, Joonwoo (Horticulture, environment and biotechnology, 2025)
Nitrogen is crucial for crop development and plays a pivotal role in various physiological processes, particularly photosynthesis. Its significance in agriculture is underscored by its extensive use as a chemical fertilizer. However, a comprehensive quantitative assessment of the photosynthetic processes and nitrogen allocation in leaves with respect to nitrogen supply levels remains elusive. Thus, in this study, we aimed to quantitatively evaluate the changes in photosynthetic traits and nitrogen distribution across varying nitrogen fertilization levels. Hydroponically cultivated romaine lettuce ( Lactuca sativa L. var. longifolia ) served as the experimental subjects. concentrations of 75 (75 N), 50 (50 N), 25 (25 N), and 0 (0 N)% were prepared from the standard nutrient solution with an concentration of 100 (CON)%. The photosynthetic traits across different nitrogen fertilization levels in each treatment were assessed, and the photosynthetic rate in response to changes in CO 2 concentration and light intensity was measured using a portable photosynthesis system. These data were fitted to the Farquhar, von Caemmerer, and Berry (FvCB) model to derive photosynthetic parameters, particularly the maximum carboxylation capacity ( V cmax ) and maximum electron transport rate ( J max ). Furthermore, to examine nitrogen distribution with respect to nitrogen fertilization levels, the total nitrogen, chlorophyll, and ribulose-1,5-bisphosphate carboxylase/oxygenase (rubisco) contents were measured. With increasing nitrogen fertilization levels from 0 to 75 N, notable enhancements were observed in V cmax , J max , total nitrogen content, and chlorophyll content. Nevertheless, the rubisco content exhibited no significant variance across treatments, except in the control group. The analysis of growth and photosynthesis with respect to nitrogen fertilization levels revealed that even with a 75 N reduction in nitrogen concentration, J max displayed less susceptibility than V cmax . Diminishing nitrogen content precipitated reductions in rubisco and chlorophyll contents, leading to a rapid decrease in V cmax and subsequently influencing J max .